Factors affecting customer satisfaction and retention in retail store - Panirchelvam, Dinesh (2021)
Retail success in today’s competitive market requires a great understanding and respect of the customers. Retail stores have undergone drastic changes and developments, whereby the importance of customer satisfaction and customer retention has become retailers’ main concern. This is because there is still a lack of study to explain how customer satisfaction and retention can be develop by retailers in sustaining competitive advantage against online shopping. Therefore, customer satisfaction and customer retention have been identified as important elements for a retail store to generate good sales and healthy profits. Studies about customer satisfaction and retention in retail store had been done previously but continue to remain scarce. This research identifies the factors affecting customer satisfaction and retention in retail store. Specifically, factors such as promotional mix, service quality, psychological factor and product quality are taken into consideration in order to study their effect on customer satisfaction and retention in retail store. The Kano Model and Maslow Hierarchy of Needs were identified as the two most significant theories of this research. Quantitative method was used to collect and analyze data to test the hypotheses. The sampling method used in this research is convenience sampling. University students was chosen as the target respondents whereby N=220 students were selected from the total population of 12,000 based on table of sample size determining by Krejcie and Morgan. A standard survey questionnaire adapted from previous research was distributed to the respondents and SPSS were used as an instrument to identify and examine the information and data collected from the questionnaires. It was found that factors such as promotional mix, service quality, psychological factor and product quality have a significant effect on customer satisfaction and retention in retail store. Based on the research outcome, a framework of factors affecting customer satisfaction and retention in retail store was developed. This research also contributes to the theoretical and practical implications. This research finding is valuable to the retailers as they can focus to invest ideas and efforts that create effective business strategies to attract more customers. Therefore, retailers must take significant measures that enhance retail store’s competency in giving best values to the customers. Moreover, sustainability of retail stores tends to create more employment opportunities and new career prospects.